PENINGKATAN HASIL BELAJAR SISWA DENGAN METODE EKSPERIMEN PADA PEMBELAJARAN IPA TEMA BENDA-BENDA DI LINGKUNGAN SEKITAR DI KELAS V UPT. SD NEGERI 18 BARINGIN - Maisuardi Maisuardi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
This research is motivated by the problems that the authors found at UPT. SD Negeri 18 Baringin. These problems are obtained from the results of observations and observations of the author in the field, where the learning process shows that students are less active in the learning process, the difficulty of students in remembering the material that has been studied. The objectives of this study were (1) to determine teacher activity using experimental methods, (2) to determine student activity using experimental methods, (3) to determine student learning outcomes using experimental methods in science learning in class V UPT. SD Negeri 18 Baringin. This research uses classroom action research (PTK) with the subject of students of class V UPT. SD Negeri 18 Baringin which consists of 23 students. Based on the results of the research data analysis, it was found that (1) Teacher activity in cycle I was 70% (good category), and increased in cycle II by 83.2% (very good category), (2) Student activity in cycle I was 69.2% were in (good category), and increased in cycle II by 84.8% (very good category), (3) Student learning outcomes in cycle I were 69.6% (Good Enough), and increased in cycle II amounted to 87% (very good category). Thus it can be concluded that the use of the experimental method in science lessons to improve the learning outcomes of class V UPT students. SD Negeri 18 Baringin. has been accomplished.